Ternary positive electrode material preparation method, obtained ternary positive electrode material and lithium ion battery

During the synthesis of nickel-cobalt lithium manganate ternary cathode material, the core-shell nanointermediates were prepared using co-precipitation reaction and grown and aged, the material defects caused by excessively long diffusion paths were solved, and the cycle stability and electrochemical properties of the material were significantly improved.

CN119695136AActive Publication Date: 2025-03-25安徽得壹能源科技有限公司
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411862297.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

During the synthesis process, the existing nickel-cobalt lithium manganate ternary cathode materials have a long diffusion path of lithium ions, resulting in defects, lattice distortion and lattice stress during the growth of the material crystal, which in turn affects its electrochemical performance.

Method used

Core-shell nanointermediates were prepared by passing the nano-scale lithium salt suspension into the ternary precursor mother liquor, performing co-precipitation reaction, and undergoing growth and aging treatment, and finally mixed with the lithium source to calcinate the ternary positive electrode material.

Benefits of technology

This method effectively shortens the diffusion path of lithium ions, improves the lattice stress and defects of the material, and improves the cyclic stability and electrochemical properties of the ternary cathode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695136A_ABST
    Figure CN119695136A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a ternary positive electrode material, the obtained ternary positive electrode material and a lithium ion battery, and belongs to the technical field of lithium ion battery electrode materials. The preparation method comprises the following steps: introducing a nanoscale lithium salt suspension into a ternary precursor mother solution, and uniformly mixing to obtain a mixed dispersion liquid; a nickel salt solution, a cobalt salt solution and a manganese salt solution are introduced into the mixed dispersion liquid, the pH value is adjusted, a co-precipitation reaction is carried out, and a core-shell nanometer intermediate is obtained; growing and aging the core-shell nano intermediate to obtain a pre-lithium precursor; and mixing the pre-lithium precursor with a lithium source, and calcining in an oxygen-containing atmosphere to obtain the ternary positive electrode material. In the coprecipitation process, the nanoscale non-water-soluble or slightly-water-soluble lithium salt is used as a crystal nucleus, and the method can effectively shorten the lithium ion diffusion path length in the production process of the ternary positive electrode material, so that the prepared ternary positive electrode material has excellent cycling stability when being applied to a lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery electrode materials, and in particular to a method for preparing a ternary positive electrode material and the obtained ternary positive electrode material and a lithium ion battery. Background Art

[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] With the rapid growth of electric vehicles in recent years, the problem of battery life anxiety has become increasingly prominent, and the demand for lithium batteries with higher energy density materials is increasing. Nickel-cobalt-manganese oxide lithium ternary cathode materials have a high reversible energy density, which to a certain extent meets people's needs for long battery life and has been widely studied and applied in recent years.

[0004] The existing method for synthesizing nickel-cobalt-manganese-oxide lithium ternary positive electrode materials mainly adopts the physical mixing of nickel-cobalt-manganese-oxide ternary precursor and lithium source (lithium carbonate or lithium hydroxide) and then solid-phase sintering to prepare nickel-cobalt-manganese-oxide lithium ternary positive electrode materials. During the high-temperature calcination process, the molten lithium source wraps the solid nickel-cobalt-manganese-oxide lithium ion, and the lithium ions diffuse into the nickel-cobalt-manganese-oxide ternary precursor. At this time, due to the long diffusion path of lithium ions and the large steric hindrance, the nickel-cobalt-manganese-oxide lithium ternary positive electrode material crystals will produce defects, lattice distortion and lattice stress to varying degrees during growth at the microscopic level, which will lead to poor electrochemical performance of the nickel-cobalt-manganese-oxide lithium ternary positive electrode material at the macroscopic level, such as low capacity, low efficiency, poor cycle life and other problems.

[0005] Therefore, how to provide a method for preparing a nickel-cobalt-manganese-oxide lithium ternary positive electrode material to improve the electrochemical performance of the nickel-cobalt-manganese-oxide lithium ternary positive electrode material is an urgent problem to be solved. Summary of the invention

[0006] In view of this, the present invention provides a method for preparing a ternary positive electrode material and the obtained ternary positive electrode material and a lithium ion battery. The preparation method provided by the present invention can effectively shorten the length of the lithium ion diffusion path during the production process of the nickel cobalt lithium manganese oxide ternary positive electrode material, thereby improving the lattice stress and lattice defects of the ternary positive electrode material and improving the electrochemical performance of the ternary positive electrode material.

[0007] In a first aspect, the present invention provides a method for preparing a ternary positive electrode material, comprising the following steps:

[0008] S1, passing the nano-scale lithium salt suspension into the ternary precursor mother solution and mixing them evenly to obtain a mixed dispersion; the nano-scale lithium salt is a water-insoluble or slightly water-soluble lithium salt; the D50 of the nano-scale lithium salt is 10 to 50 nm;

[0009] S2, respectively introducing nickel salt, cobalt salt and manganese salt solutions into the mixed dispersion, adjusting the pH value to cause a coprecipitation reaction, and obtaining a core-shell nano intermediate, wherein the D50 of the core-shell nano intermediate is controlled to be 50-100 nm; the core of the core-shell nano intermediate is a nano-scale lithium salt, and the shell is a nickel-cobalt-manganese hydroxide;

[0010] S3, growing and aging the core-shell nano intermediate to obtain a pre-lithium precursor, wherein the mass fraction of lithium element in the pre-lithium precursor is 1 to 3 wt%;

[0011] S4. Mix the pre-lithium precursor with a lithium source, and calcine the mixture in an oxygen-containing atmosphere to obtain a ternary positive electrode material.

[0012] Preferably, the nanoscale lithium salt is selected from one or more of lithium carbonate, lithium fluoride or lithium phosphate.

[0013] Preferably, the content of lithium element in the nanoscale lithium salt suspension in step S1 is 15-30 g / L.

[0014] Preferably, in step S2, the molar ratio of nickel element, cobalt element and manganese element is (3-7):(1-3):(1-3).

[0015] Preferably, in step S2, the pH value is 10-13; the nickel source is selected from one or more of nickel sulfate, nickel chloride, nickel nitrate, nickel oxalate, nickel acetate or nickel citrate; the cobalt source is selected from one or more of cobalt sulfate, cobalt chloride, cobalt nitrate, cobalt oxalate, cobalt acetate or cobalt citrate; the manganese source is selected from one or more of manganese sulfate, manganese chloride, manganese nitrate, manganese oxalate, manganese acetate or manganese citrate.

[0016] Preferably, the growth process of step S3 is carried out under the conditions of pH 9-11, temperature 45-60°C, stirring speed 500-900r / min, and the growth time is 5-50h; the aging process is carried out under the conditions of temperature 45-60°C, rotation speed 150-300r / min, and the aging time is 10-15h; the D50 of the pre-lithium precursor is 4-10μm.

[0017] Preferably, in step S4, the lithium source is selected from one or more of lithium carbonate, lithium hydroxide, lithium oxalate, lithium acetate or lithium oxide; the ratio of the lithium element in the lithium source to the total molar amount of nickel, cobalt and manganese elements in the pre-lithium precursor is (1.03-1.08):1.

[0018] Preferably, the calcination temperature is 700-950° C., and the calcination time is 8-15 hours.

[0019] In a second aspect, the present invention provides a ternary positive electrode material prepared by the above preparation method.

[0020] In a third aspect, the present invention provides a lithium-ion battery comprising the above-mentioned ternary positive electrode material.

[0021] Compared with the prior art, the present invention has achieved the following beneficial effects:

[0022] The present invention uses nanometer-level water-insoluble or slightly water-soluble lithium salt as a crystal nucleus, and prepares a core-shell nano intermediate with nanometer-level water-insoluble or slightly water-soluble lithium salt as a core and nickel-cobalt-manganese hydroxide as an outer shell through a coprecipitation reaction, and then grows and ages it, and then calcines it with a lithium source to obtain a ternary positive electrode material. Since the coprecipitation process of the present invention uses nanometer-level water-insoluble or slightly water-soluble lithium salt as a crystal nucleus, the lithium salt is wrapped in the formed ternary positive electrode material. The method can effectively shorten the length of the lithium ion diffusion path in the production process of the ternary positive electrode material, thereby achieving the purpose of improving the lattice stress and lattice defects of the positive electrode material. The finally prepared ternary positive electrode material has excellent cycle stability when applied to lithium ion batteries. Under the charge and discharge conditions of 0.5C / 1C, the capacity retention rate of 50 cycles is more than 90%, and the capacity retention rate of 100 cycles is more than 85%, which is much better than the cycle performance of the ternary positive electrode material without pre-lithium modification. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The drawings constituting part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation of the present invention. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0024] Figure 1 It is a test chart of the cycle performance of batteries assembled with the ternary positive electrode materials of Examples 1-2 of the present invention and Comparative Examples 1-2. DETAILED DESCRIPTION

[0025] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0026] As introduced in the background technology, in the synthesis process of the existing nickel-cobalt-manganese-lithium ternary positive electrode material, the nickel-cobalt-manganese ternary precursor and the lithium source are directly solid-phase sintered to prepare the nickel-cobalt-manganese-lithium ternary positive electrode material. During the solid-phase sintering process, the lithium ions migrate into the precursor under the trend of thermal energy, but the precursor is still in a non-liquid state at this time, which makes it more difficult for the lithium ions to migrate into the non-liquid precursor. First, the migration path is long, and second, the steric hindrance is large; therefore, this method will cause the nickel-cobalt-manganese-lithium ternary positive electrode material crystal to produce defects, lattice distortion and lattice stress to varying degrees during growth, which leads to poor macroscopic electrochemical performance. Therefore, the present invention provides a method for preparing a ternary positive electrode material, comprising the following steps:

[0027] S1, passing the nano-scale lithium salt suspension into the ternary precursor mother solution and mixing them evenly to obtain a mixed dispersion; the nano-scale lithium salt is a water-insoluble or slightly water-soluble lithium salt; the D50 of the nano-scale lithium salt is 10 to 50 nm;

[0028] S2, respectively introducing nickel salt, cobalt salt and manganese salt solutions into the mixed dispersion, adjusting the pH value to cause a coprecipitation reaction, and obtaining a core-shell nano intermediate, wherein the D50 of the core-shell nano intermediate is controlled to be 50-100 nm; the core of the core-shell nano intermediate is a nano-scale lithium salt, and the shell is a nickel-cobalt-manganese hydroxide;

[0029] S3, growing and aging the core-shell nano intermediate to obtain a pre-lithium precursor, wherein the mass fraction of lithium element in the pre-lithium precursor is 1 to 3 wt%;

[0030] S4. Mix the pre-lithium precursor with a lithium source, and calcine the mixture in an oxygen-containing atmosphere to obtain a ternary positive electrode material.

[0031] In the present invention, since the selected lithium salt is a water-insoluble or slightly water-soluble lithium salt, it can be directly used as a crystal nucleus for a coprecipitation reaction, and nickel-cobalt-manganese hydroxide is grown thereon by a coprecipitation method, thereby obtaining a nano intermediate with a core-shell structure; this method ensures that each precursor particle contains a lithium salt, and when the pre-lithium precursor containing the lithium salt is calcined with a lithium source, the migration path of lithium ions in the subsequent calcination process can be shortened, and then the defects and lattice stress inside the material can be improved to a certain extent, thereby achieving the effect of improving the cycle life of the ternary positive electrode material.

[0032] The present invention does not impose any special restrictions on the ternary precursor mother solution, which is a solution separated from the process of preparing the nickel-cobalt-manganese ternary precursor by coprecipitation, and contains a small amount of nickel, cobalt, and manganese metal ions. In the nanoscale lithium salt suspension in step S1 of the present invention, the content of lithium element is 15 to 30 g / L. The present invention does not impose any special restrictions on the amount of the ternary precursor mother solution, and it can be adjusted according to actual conditions to control the pre-lithiation process.

[0033] In the present invention, the nanometer-scale lithium salt is selected from one or more of lithium carbonate, lithium fluoride or lithium phosphate, and is more preferably lithium carbonate; the D50 of the nanometer-scale lithium salt is 10 to 50 nm.

[0034] In step S2 of the present invention, the molar ratio of nickel element, cobalt element and manganese element is (3-7):(1-3):(1-3). In one or more embodiments of the present invention, the molar ratio of nickel element, cobalt element and manganese element is 6:2:2. The present invention does not impose any special restrictions on the concentrations of nickel salt, cobalt salt and manganese salt solutions. The concentrations of nickel salt, cobalt salt and manganese salt solutions commonly used in the art can be used. Preferably, the concentration of the nickel salt is 1-3 mol / L, the concentration of the cobalt salt is 1-3 mol / L, and the concentration of the manganese salt is 1-3 mol / L. The introduction of nickel salt, cobalt salt and manganese salt solutions is beneficial to control the core-shell nano intermediate and the degree of pre-lithiation.

[0035] In step S2 of the present invention, the pH value is 10-13. The present invention does not impose any special restrictions on the method of adjusting the pH value, and the method of adjusting the pH value commonly used in the art can be used, for example, one or more of sodium hydroxide, ammonia water, and potassium hydroxide are used for pH adjustment.

[0036] In the present invention, the nickel source is selected from one or more of nickel sulfate, nickel chloride, nickel nitrate, nickel oxalate, nickel acetate or nickel citrate; the cobalt source is selected from one or more of cobalt sulfate, cobalt chloride, cobalt nitrate, cobalt oxalate, cobalt acetate or cobalt citrate; the manganese source is selected from one or more of manganese sulfate, manganese chloride, manganese nitrate, manganese oxalate, manganese acetate or manganese citrate.

[0037] The growth process of step S3 of the present invention is carried out under the conditions of pH 9-11, temperature 45-60°C, stirring speed 500-900r / min, and the growth time is 5-50h; the aging process is carried out under the conditions of temperature 45-60°C, rotation speed 150-300r / min, and the aging time is 10-15h. The D50 of the pre-lithium precursor is 4-10μm.

[0038] In step S4 of the present invention, the lithium source is selected from one or more of lithium carbonate, lithium hydroxide, lithium oxalate, lithium acetate or lithium oxide; the ratio of the lithium element in the lithium source to the total molar amount of nickel, cobalt and manganese elements in the pre-lithium precursor is (1.03-1.08):1.

[0039] In the present invention, the calcination temperature is 700-950°C, and the calcination time is 8-15 hours. The present invention does not impose any special restrictions on the oxygen-containing atmosphere, and the calcination can be carried out in air or in an oxygen atmosphere.

[0040] The present invention also provides a ternary positive electrode material prepared by the above preparation method.

[0041] The present invention also provides a lithium-ion battery, comprising the above-mentioned ternary positive electrode material.

[0042] The present invention does not impose any particular limitation on the preparation method of the lithium ion battery, and any preparation method of lithium ion batteries commonly used in the art may be used.

[0043] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0044] Example 1

[0045] This embodiment provides a method for preparing a nickel-cobalt-lithium manganese oxide ternary positive electrode material.

[0046] (1) A suspension prepared from nano-scale lithium carbonate (the D50 of the lithium salt is 50 nm, and the lithium content is 20 g / L calculated as lithium element) is introduced into the precursor mother liquor and fully stirred to mix the lithium salt suspension with the ternary precursor mother liquor to obtain a mixed dispersion. The lithium content in the mixed dispersion is 10 g / L calculated as lithium element.

[0047] (2) According to the designed ratio (the molar ratio of nickel, cobalt and manganese is Ni: Co: Mn = 6: 2: 2), 2 mol / L nickel sulfate solution, 2 mol / L cobalt sulfate solution and 2 mol / L manganese sulfate solution are slowly introduced respectively under high-speed stirring, and the pH value is adjusted to 11.0-11.5 with alkali solution (NaOH concentration is 8 M, ammonia concentration is 20 g / L), so that nickel, cobalt and manganese hydroxides are co-precipitated with nano-scale lithium carbonate as crystal nuclei, thereby forming a nano-scale ternary precursor intermediate with a nano-scale lithium salt as the inner core and nickel, cobalt and manganese hydroxide as the outer layer, and the D50 of the intermediate is controlled to be 100 nm;

[0048] (3) The liquid containing the ternary precursor intermediate is transferred to another reactor to grow and age the ternary precursor. The growth process is carried out at a pH of 10 to 10.5, a temperature of 50°C, a stirring speed of 700 r / min, and a growth time of 20 h. The aging process is carried out at a temperature of 50°C and a rotation speed of 200 r / min, and the aging time is 12 h. After filtering and drying, a nickel-cobalt-manganese oxide having a D50 of 4 μm and containing a certain amount of lithium salt is finally obtained, i.e., a pre-lithium precursor (wherein the mass fraction of lithium is 3 wt%).

[0049] (4) The above-mentioned pre-lithium precursor is mixed with a certain amount of lithium carbonate so that the total molar ratio of lithium element to nickel, cobalt and manganese element is 1.05 (i.e., n Li :n (Ni+Co+Mn)=1.05), then heated to 870°C in an air atmosphere, calcined for 12 hours, and after crushing, screening and demagnetization, a positive electrode material prepared with a pre-lithium precursor was obtained.

[0050] Example 2

[0051] This embodiment provides a method for preparing a nickel-cobalt-lithium manganese oxide ternary positive electrode material.

[0052] (1) A suspension prepared from nano-scale lithium carbonate (the D50 of the lithium salt is 30 nm, and the lithium content is 20 g / L calculated as lithium element) is introduced into the precursor mother liquor and stirred thoroughly to mix the lithium salt suspension and the ternary precursor mother liquor thoroughly to obtain a mixed dispersion. The lithium content in the mixed dispersion is 10 g / L calculated as lithium element.

[0053] (2) According to the designed ratio (the molar ratio of nickel, cobalt and manganese is Ni: Co: Mn = 6: 2: 2), 2 mol / L nickel nitrate solution, 2 mol / L cobalt nitrate solution and 2 mol / L manganese nitrate solution are slowly introduced respectively under high-speed stirring, and the pH value is adjusted to 11.0-11.5 with alkaline solution (NaOH concentration is 8 M, ammonia concentration is 20 g / L), so that nickel, cobalt and manganese hydroxides are co-precipitated with nano-scale lithium carbonate as crystal nuclei, thereby forming a nano-scale ternary precursor intermediate with a nano-scale lithium salt as the inner core and nickel, cobalt and manganese hydroxide as the outer layer, and the D50 of the intermediate is controlled to be 80 nm;

[0054] (3) The liquid containing the ternary precursor intermediate is transferred to another reactor to grow and age the ternary precursor. The growth process is carried out at a pH of 10 to 10.5, a temperature of 50°C, a stirring speed of 700 r / min, and a growth time of 20 h. The aging process is carried out at a temperature of 50°C and a rotation speed of 200 r / min, and an aging time of 12 h. After filtering and drying, a nickel-cobalt-manganese oxide having a D50 of 7 μm and containing a certain amount of lithium salt is finally obtained, i.e., a pre-lithium precursor (wherein the mass fraction of lithium is 2 wt%).

[0055] (4) The above-mentioned pre-lithium precursor is mixed with a certain amount of lithium carbonate so that the total molar ratio of lithium element to nickel, cobalt and manganese elements is 1.03 (i.e., n Li :n (Ni+Co+Mn) =1.03), then heated to 870°C in an air atmosphere, calcined for 12 hours, and after crushing, screening and demagnetization, a positive electrode material prepared with a pre-lithium precursor was obtained.

[0056] Example 3

[0057] This embodiment provides a method for preparing a nickel-cobalt-lithium manganese oxide ternary positive electrode material.

[0058] (1) A certain amount of suspension prepared from nano-scale lithium carbonate (the D50 of the lithium salt is 10 nm) is introduced into the precursor mother liquor and stirred thoroughly to mix the lithium salt suspension and the ternary precursor mother liquor thoroughly and evenly to obtain a mixed dispersion. The content of lithium in the mixed dispersion is 10 g / L, calculated as lithium element.

[0059] (2) According to the designed ratio (the molar ratio of nickel, cobalt and manganese is Ni: Co: Mn = 6: 2: 2), 2 mol / L nickel sulfate solution, 2 mol / L cobalt sulfate solution and 2 mol / L manganese sulfate solution are slowly introduced respectively under high-speed stirring, and the pH value is adjusted to 11.0-11.5 with alkali solution (NaOH concentration is 8 M, ammonia concentration is 20 g / L), so that nickel, cobalt and manganese hydroxides are co-precipitated with nano-scale lithium carbonate as crystal nuclei, thereby forming a nano-scale ternary precursor intermediate with a nano-scale lithium salt as the inner core and nickel, cobalt and manganese hydroxide as the outer layer, and the D50 of the intermediate is controlled to be 50 nm;

[0060] (3) The liquid containing the ternary precursor intermediate is transferred to another reactor to grow and age the ternary precursor. The growth process is carried out at a pH of 10 to 10.5, a temperature of 50°C, a stirring speed of 700 r / min, and a growth time of 20 h. The aging process is carried out at a temperature of 50°C and a rotation speed of 200 r / min, and an aging time of 12 h. After filtering and drying, a nickel-cobalt-manganese oxide having a D50 of 10 μm and containing a certain amount of lithium salt is finally obtained, i.e., a pre-lithium precursor (wherein the mass fraction of lithium is 1 wt%).

[0061] (4) The above-mentioned pre-lithium precursor is mixed with a certain amount of lithium carbonate so that the total molar ratio of lithium element to nickel, cobalt and manganese element is 1.06 (i.e., n Li :n (Ni+Co+Mn) =1.06), and then calcined in an air atmosphere, and after crushing, screening and demagnetization, a positive electrode material prepared with a pre-lithium precursor was obtained.

[0062] Comparative Example 1

[0063] This embodiment provides a method for preparing a nickel-cobalt-lithium manganese oxide ternary positive electrode material.

[0064] (1) According to the designed ratio (the molar ratio of nickel, cobalt and manganese is Ni: Co: Mn = 6: 2: 2), 2 mol / L nickel sulfate solution, 2 mol / L cobalt sulfate solution and 2 mol / L manganese sulfate solution are slowly introduced respectively under high-speed stirring, and the pH value is adjusted to 11.0-11.5 with alkaline solution (NaOH concentration is 8 M, ammonia concentration is 20 g / L), so that nickel, cobalt and manganese hydroxides are coprecipitated to form a nano-scale ternary precursor intermediate, and the D50 of the intermediate is controlled to be 100 nm;

[0065] (2) The liquid containing the ternary precursor intermediate is transferred to another reactor to grow and age the ternary precursor. The growth process is carried out at a pH of 10 to 10.5, a temperature of 50°C, a stirring speed of 700 r / min, and a growth time of 20 h. The aging process is carried out at a temperature of 50°C and a rotation speed of 200 r / min, and an aging time of 12 h. After filtering and drying, a nickel-cobalt-manganese oxide with a D50 of 4 μm, i.e., a precursor, is finally obtained.

[0066] (3) The above-mentioned pre-lithium precursor is mixed with a certain amount of lithium carbonate so that the total molar ratio of lithium element to nickel, cobalt and manganese elements is 1.05 (i.e., n Li :n (Ni+Co+Mn) =1.05), then heated to 870°C in an air atmosphere, calcined for 12 hours, and after crushing, screening and demagnetization, a positive electrode material prepared with a pre-lithium precursor was obtained.

[0067] Comparative Example 2

[0068] The commercially available NCM622 precursor (D50 is 4 μm) was mixed with a certain amount of lithium carbonate so that the total molar ratio of lithium to nickel, cobalt and manganese elements was 1.05 (i.e., n Li :n (Ni+Co+Mn) =1.05), then heated to 870°C in an air atmosphere, calcined for 12 hours, and after crushing, screening and demagnetization, a positive electrode material prepared with a pre-lithium precursor was obtained.

[0069] Test example

[0070] Preparation of button cells: The positive electrode materials prepared in the above-mentioned Examples 1 to 2 and Comparative Examples 1 to 2 are respectively assembled as button cells, as follows: the ternary positive electrode material, the conductive agent (acetylene black) and the binder (PVDF) are weighed in a mass ratio of 90:5:5, and the weighed positive electrode material and acetylene black are mixed and ground in an agate mortar, and after grinding evenly, they are added to N-methylpyrrolidone (NMP) that has been fully reacted with PVDF and continuously ground until the slurry becomes a viscous liquid with a certain fluidity. The ground slurry is evenly transferred to aluminum foil, and the sample is evenly coated with a coater with a thickness of 300 μm, and then pre-baked in air at 60°C for 5 hours, and then vacuumed and dried at 90°C for 12 hours to achieve the purpose of removing water and organic matter in the coated sample, and the electrode sheet is cut out according to size for use to obtain the positive electrode sheet. The lithium sheet was used as the negative electrode, the prepared electrode sheet was used as the positive electrode, the electrolyte ratio was EC:DMC=1:1, and button cells were assembled. The charge and discharge test was performed using a BTV charge and discharge tester. At 25°C, the lithium-ion battery assembled with the above positive electrode sheet was charged and discharged at 0.5C / 1C at a working voltage of 3.0-4.4V. The test results are shown in Table 1 and Figure 1shown.

[0071] Table 1 Cyclic performance of batteries assembled with ternary cathode materials of the embodiments and comparative examples

[0072]

[0073] From Table 1 and Figure 1 It can be seen that the battery assembled with the ternary positive electrode material that has been pre-lithium treated has excellent cycle performance, which is far better than the battery assembled with the ternary positive electrode material that has not been pre-lithium treated. The capacity retention rate of 100 cycles is increased by more than 90%, and the effect is very significant.

[0074] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a ternary positive electrode material, characterized in that: The steps include: S1, passing the nano-scale lithium salt suspension into the ternary precursor mother solution and mixing them evenly to obtain a mixed dispersion; the nano-scale lithium salt is a water-insoluble or slightly water-soluble lithium salt; the D50 of the nano-scale lithium salt is 10 to 50 nm; S2, respectively introducing nickel salt, cobalt salt and manganese salt solutions into the mixed dispersion, adjusting the pH value to cause a coprecipitation reaction, and obtaining a core-shell nano intermediate, wherein the D50 of the core-shell nano intermediate is controlled to be 50-100 nm; the core of the core-shell nano intermediate is a nano-scale lithium salt, and the shell is a nickel-cobalt-manganese hydroxide; S3, growing and aging the core-shell nano intermediate to obtain a pre-lithium precursor, and controlling the mass fraction of lithium in the pre-lithium precursor to be 1-3wt%; S4. Mix the pre-lithium precursor with a lithium source, and calcine the mixture in an oxygen-containing atmosphere to obtain a ternary positive electrode material.

2. The preparation method according to claim 1, characterized in that The nanoscale lithium salt is selected from one or more of lithium carbonate, lithium fluoride or lithium phosphate.

3. The preparation method according to claim 1, characterized in that: In the nano-scale lithium salt suspension in step S1, the content of lithium element is 15-30 g / L.

4. The preparation method according to claim 1, characterized in that: In step S2, the molar ratio of nickel element, cobalt element and manganese element is (3-7):(1-3):(1-3).

5. The preparation method according to claim 1, characterized in that: In step S2, the pH value is 10-13; the nickel source is selected from one or more of nickel sulfate, nickel chloride, nickel nitrate, nickel oxalate, nickel acetate or nickel citrate; the cobalt source is selected from one or more of cobalt sulfate, cobalt chloride, cobalt nitrate, cobalt oxalate, cobalt acetate or cobalt citrate; the manganese source is selected from one or more of manganese sulfate, manganese chloride, manganese nitrate, manganese oxalate, manganese acetate or manganese citrate.

6. The preparation method according to claim 1, characterized in that: The growth process of step S3 is carried out under the conditions of pH 9-11, temperature 45-60°C, stirring speed 500-900r / min, and the growth time is 5-50h; the aging process is carried out under the conditions of temperature 45-60°C, rotation speed 150-300r / min, and the aging time is 10-15h; the D50 of the pre-lithium precursor is 4-10μm.

7. The preparation method according to claim 1, characterized in that: In step S4, the lithium source is selected from one or more of lithium carbonate, lithium hydroxide, lithium oxalate, lithium acetate or lithium oxide; the ratio of the lithium element in the lithium source to the total molar amount of nickel, cobalt and manganese elements in the pre-lithium precursor is (1.03-1.08):

1.

8. The preparation method according to claim 1, characterized in that: The calcination temperature is 700-950° C., and the calcination time is 8-15 hours.

9. The ternary positive electrode material prepared by the preparation method according to any one of claims 1 to 8.

10. A lithium ion battery, characterized in that: Including the ternary positive electrode material as described in claim 9.

Citation Information

Patent Citations

  • Preparation method of lithium manganate precursor as lithium ion battery anode material

    CN102324516A

  • Core-shell structure NCM (nickel manganese cobalt) ternary cathode material containing carbon nanotube and preparation method thereof

    CN108539193A

  • Nickel-cobalt-manganese ternary cathode material, preparation method and application thereof, lithium ion battery, electric vehicle

    CN109244431A

  • Lithium-containing ternary precursor and preparation method thereof, ternary cathode material and preparation method thereof, and lithium ion battery

    CN112133890A

  • High-nickel ternary precursor, positive electrode material and preparation method thereof

    CN112250091A